Analisis Tingkat Berfikir Kreatif Peserta Didik Dalam Menyelesaikan Soal Matematika Ditinjau Dari Adversity Quotient (AQ) - Duwi Asih asih; I Ketut Suastika; Nyamik Rahayu Sesanti (RAINSTEK : Jurnal Terapan Sains & Teknologi, 2019)
ABSTRAK. The aim of this paper is to describe students' creative thinking abilities in solving problems in terms of Adversity Quotient (AQ). This study used a descriptive qualitative approach with questionnaire and test method. The subjects of this study were SMP Turen Muhammadiyah 10 class VIII, who were selected based on their Adversity Quotient (AQ). The results of this paper are (1) the questionnaire score of the Adversity Response Profile (ARP) shows 6 students with the type of quitters, 7 transitional type students between quitters to campers, 9 students with type campers, 6 students with transition types of campers to climbers , 4 students with type climbers. (2) The written test results showed students with AQ type climbers included in the "high" category, AQ type campers included as "low" category, AQ type quitters including "very low" level categories in creative thinking. Suggestions from this study are teachers are expected to provide exercises with various types of questions to improve students' creative thinking skills. Keywords: Analize; cretive thinking; Adversity Quotient (AQ) ABSTRAK. Tujuan dari penelitian ini adalah untuk mendeskripsikan kemampuan berfikir kreatif peserta didik dalam menyelesaikan masalah ditinjau dari Adversity Quotient (AQ). Penelitian ini menggunakan pendekatan kualitatif yang bersifat deskriptif dengan metode angket, tes . Subyek penelitian ini adalah peserta didik kelas VIII SMP Muhammadiyah 10 Turen yang dipilih berdasarkan Adversity Quotient (AQ) secara acak. Hasil penelitian ini yaitu (1) skor angket Adversity Respone Profile (ARP) menunjukkan 6 peserta didik dengan tipe quitters, 7 peserta didik dengan tipe peralihan antara quitters ke campers, 9 peserta didik dengan tipe campers, 6 peserta didik dengan tipe peralihan campers ke climbers, 4 peserta didik dengan tipe climbers. (2) Hasil tes tulis menunjukkan peserta didik dengan AQ tipe climbers termasuk kategori tingkat “tinggi”, AQ tipe campers termasuk kategori tingkat “rendah”, AQ tipe quitters termasuk kategori tingkat “sangat rendah” dalam berfikir kreatif. Saran dari penelitian ini adalah guru diharapkan memberikan latihan-latihan dengan berbagai jenis soal untuk meningkatkan kemampuan berfikir kreatif peserta didik. Kata Kunci: Analisis; berfikir kreatif; Adversity Quotient (AQ)